EFFECT OF VINEGER ADDED TO DRINKING WATER ON THE BROILER PERFORMANCE DURING SUMMER SEASON: Mohammad J.B. Al- Shadeed; Shahrazad M. Al-Shadeed* Najim I. Al-Hadeethi and Ammar. Q. Al-Awssi - Al- Shadeed, Mohammad J.B. (The Iraqi Journal of Veterinary Medicine, 2010)
This study was conducted at poultry farm of the College of Agriculture, University of Baghdad during the period from the 21st of July to 26th of August of 2001 toidentify the effects of vineger on broiler performance at the two weeks of breeding period during summer season. One hundred and twenty unsexed faw-bro broiler chicks divided randomly into two equal groups consisted of 60 chicks in each (3 replicate of 20 chicks each ) they were exposed to one of the following treatments:– Treatment 1: tap water for the 7 and 8 weeks of age.- Treatment 2: water + vineger (0.1%) for the same period.The results showed that treat.2 enhanced significantly (P<0.05) body weight compared with treat.1 . The mean body weight were 1200 and 1150 gm at 7 weeks of age and 1500 , 1400 at 8 weeks of age respectively. Also adding 0.1% vineger to drinking water improved significantly (P<0.05) feed intake, feed conversion and decreased mortality at 7 and 8 weeks of age